2017
DOI: 10.1016/j.ymthe.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Circulating Extracellular Vesicles as a Novel Therapeutic Strategy against Cancer Metastasis

Abstract: Metastasis is the main cause of cancer mortality for many types of cancer; however, difficulties remain in effectively preventing metastasis. It has been recently and widely reported that cancer-derived extracellular vesicles (EVs) contribute to cancer metastasis. Thus, therapeutic strategies targeting cancerderived EVs hold great promise because of the possibility of EVs driving the cancer microenvironment toward metastasis. Here, we provide a novel strategy for therapeutic antibody treatment to target cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(151 citation statements)
references
References 48 publications
2
148
0
1
Order By: Relevance
“…If we were able to effectively inhibit the function of malignant EVs during surgery by administration of an inhibitor in the peritoneal cavity, this treatment could prevent or reduce future metastasis. As our recent report, we disrupted cancer-derived EVs by therapeutic antibody administration in a metastatic cancer mouse model and drastically suppressed metastatic cells62.…”
Section: Discussionmentioning
confidence: 75%
“…If we were able to effectively inhibit the function of malignant EVs during surgery by administration of an inhibitor in the peritoneal cavity, this treatment could prevent or reduce future metastasis. As our recent report, we disrupted cancer-derived EVs by therapeutic antibody administration in a metastatic cancer mouse model and drastically suppressed metastatic cells62.…”
Section: Discussionmentioning
confidence: 75%
“…To date, this strategy has been proposed and tested in preclinical trials. For instance, intravenous administration of monoclonal antibodies against human CD9 and CD63 depletes breast cancer derived EVs and minimizes lung‐, lymph node, and thoracic cavity oriented metastases in a xenograft mouse model . Trastuzumab (Herceptin), the therapeutic antibody specific for erb‐b2 receptor tyrosine kinase 2 (Her2), evokes diverse anticancer effects such as Her2 signaling inhibition and natural killer (NK) cell induced antibody‐dependent cell cytotoxicity (ADCC) .…”
Section: Therapeutically Targeting Evs Is a Promising Avenue In Precimentioning
confidence: 99%
“…Much like a double‐edged sword, EVs have both beneficial and adverse effects on human health, with their impact on cancer patients mostly negative. Early preclinical trials targeting EVs have demonstrated their efficacy in delaying primary tumor growth and reducing the metastatic potential, although cancer progression was not completely abolished . Thus, it remains unclear if EV‐targeting strategies hold the potential to become stand‐alone cancer therapeutics, yet they do have a strong promise to improve therapeutic outcome of cancer patients upon combination with radiation, chemotherapy, and targeted agents.…”
Section: Concluding Remarks and Prospective Vistasmentioning
confidence: 99%
See 2 more Smart Citations